pH-Controlled co-adsorption and selective separation for Cs+ and Sr2+ by an ultra-stable layered titanoniobate - Zhi-Hua Chen; Hao-Wei Lin; Bu-Bu Gao; Hai-Yan Sun; Tian-Yu Pan; Mei-Ling Feng; Xiao-Ying Huang (Chemical Engineering Journal, 2026)

Ferrihydrite sulfidation transformation reduces the mobilization of coexisting cadmium under anoxic conditions: Insights into the transformation mechanism - Xiaoming Zhao; Yifei Wang; Yu Song; Xu Ma; Ning Chen; Leo Ka Long Cheung; Ayetullah Tunc; Reza Deevsalar; Jinru Lin; Yuanming Pan; Haibo Li (Hydrometallurgy, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Targeting multidimensional nociceptor-tumor interactions to mitigate immune evasion of cancer - Aojia Jin; Jiaxing Pan; Jingyi Su; Shutong Lin; Xiaohan Shi; Yu Zhang; Jing Feng; Bruno De Geest; Twan Lammers; Tong Ji; Gang Jin; Zhiai Xu; et al. (Science Bulletin, 2026)

Directional disparity between oysters and mud snails in modulating marine carbon sequestration - Zhou Zhang; Xuan Dong; Yu-Jia Lei; Zhi-Yong Guo; Shuang-Jie Tian; Chang-Lin Li; Miao-Jun Pan; Xiang-Li Tian; Yun-Wei Dong; Jing-Yu Li; Shuang-Lin Dong (Journal of Environmental Management, 2026)

True triaxial mechanical behavior and damage mechanisms of water-saturated shale under blasting dynamic disturbance - Chongyang Wang; Sijiang Wei; Dongming Zhang; Fake Ren; Yisha Pan; Yun Lin; Yu Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Genome-wide association analysis for resistance against iridovirus disease in large yellow croaker (Larimichthys crocea) from a natural outbreak population - Ying Pan; Hongshu Chi; Nengfeng Lin; Junjia Zeng; Xiaodong Liu; Xiuxia Chen; Zaiyu Zheng; Qiuhuan Jiang; Xunkai Yu; Hui Gong (Fish & Shellfish Immunology, 2026)

Green synthesis of N-doped hierarchical porous biochar from Artemisia leaf for enhanced peroxydisulfate activation: Synergistic roles of edge nitrogen and carbonyl group - Lin Ge; Zhan Chen; Yuan Pan; Xiansheng Zhang; Teng Li; Xinyi Huang; Binbin Shao; Sheng Liu; Yunze Wang; Yu Zhang; Zhifeng Liu (Environmental Research, 2026)

Investigating the Antiviral Mechanism of Kaempferol Against Grouper Iridovirus: Combined Evaluation of In Vitro Activity and In Vivo Efficacy - Nijia Xue; Lin Huang; Jieying Yu; Jia Cai; Zhengzhao Liu; Yibing Wang; Shu Cheng; Junxiang Lai; Ying Pan; Qing Yu; Wenhong Li; Pengfei Li (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is one of the major pathogens that pose significant threats to the aquaculture industry. Kaempferol is a flavonoid compound extracted from Illicium verum Hook.f. (star anise), a material that is both edible and used in traditional medicine. In this study, we evaluated the antiviral effects of kaempferol against SGIV in vitro and in vivo, and elucidated the antiviral mechanism. Our study found that kaempferol could effectively resist SGIV infection in vitro and in vivo. Kaempferol might destroy the SGIV envelope and interfere with the attachment, invasion, and replication stages of SGIV infection. Transcriptomic analysis showed that differentially expressed genes regulated by kaempferol were enriched in ribosome, NF‐κB, and phospholipase D signalling pathways. Further screening of immunity‐related genes and pathway analysis revealed that antiviral immune responses were mainly governed by the JAK–STAT, PI3K‐Akt, and TNF signalling pathways. This study demonstrated that kaempferol exhibited significant antiviral effects against SGIV through multiple mechanisms and had the potential to become an anti‐SGIV fishery drug. These findings provide a theoretical basis for the development of effective drugs for the prevention and treatment of SGIV.

Upscaling Shock Wave Electrodialysis for Scalable Deionization - Yu-I Lin; Po-Chih Tseng; Hyunook Kim; Yupo J Lin; Shu-Yuan Pan (Water Research, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

ROMO1 loss in cholinergic neurons induces mitochondrial ultrastructural damage and ALS-like neuromuscular degeneration - Wei Nie; Zhiwen Jing; Linling Cheng; Lin-Lin Li; Yuxiao Bai; Fengli Xu; Sihan Li; Limei Lin; Xiaohui Dong; Liping Yu; Lei Cai; Bingxing Pan; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Natural deep eutectic solvents assisted the encapsulation of curcumin in gellan gum hydrogels - Yu-Nan Pan; Jia-Cheng Liu; Lin-Da Zhang; Bin Lai; Ce Wang; Jia-Nan Yan; Hai-Tao Wu (Food Research International, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Bioinspired self-assembled gradient Janus bilayer aerogel enabling coupled solar desalination and purification of multicomponent oily emulsions - Peng Pi; Yu Feng; Wen Jung Li; Ling Pan; Youxi Lin; Linxi Hou; Zihao Huang; Qinwei Wang; Xuhui Wang; Zhiying Ren (Chemical Engineering Journal, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Functional polysaccharide-based bioactive delivery systems for urinary and reproductive system therapeutics - Yung-Wei Lin; Lekshmi Rethi; Wen-Yu Pan; Hieu Trung Nguyen; Andrew E.-Y. Chuang (Drug Delivery and Translational Research, 2026)

The Antiviral Activity and Underlying Mechanisms of Quercetin in Combating Largemouth Bass Virus Infection - Lin Huang; Wenyu Liao; Mingquan Peng; Jieying Yu; Mingzhu Liu; Junxiang Lai; Ermeng Yu; Ying Pan; Fei Ling; Shuyu Han; Qing Yu; Pengfei Li (Journal of Fish Diseases, 2026)
Largemouth bass virus (LMBV), a member of the Ranavirus genus within the Iridoviridae family, is a significant pathogen causing high mortality and substantial economic losses in largemouth bass aquaculture. Therefore, developing effective antiviral agents against this viral infection is crucial for the largemouth bass aquaculture industry. Quercetin, a widely utilised flavonoid known for its therapeutic and prophylactic properties, was investigated for its antiviral efficacy against LMBV and underlying mechanisms in this study. The results demonstrated that quercetin significantly inhibited LMBV propagation in vitro and in vivo, and was effective in both prevention and treatment stages. Specifically, quercetin at 6.25 μg/mL suppressed LMBV (major capsid protein) MCP gene transcription by up to 92.09%, with the post‐infection treatment achieving 99.33% inhibition in vitro. Mechanistic studies revealed that quercetin reduces LMBV infectivity by disrupting viral internalisation and replication, while also potentiating cellular immune responses mediated by the IFN system. In vivo experiments further confirmed that quercetin treatment reduced viral transcription in the liver, spleen and kidney by 97.49%, 47.45% and 98.42%, respectively, at 48 h post‐infection and significantly enhanced the survival rate of infected juveniles. In conclusion, quercetin demonstrated potent antiviral activity against LMBV and might serve as a promising, eco‐friendly antiviral agent.

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Trophic plasticity drives species-specific adaptive responses to seasonal variability in reef-building corals - Xiao-Lei Yu; Lei Jiang; Yong Luo; Lin-Tao Huang; Peng Zhang; Zhan-Wei Li; Cheng-Yue Liu; Pan Zhang; Jian-Yu Chen; Sheng Liu; Gui-Xin Dong; Hui Huang (Coral Reefs, 2026)

Overexpression of the MsCaM1 gene from alfalfa promoted growth and salinity tolerance in transgenic Arabidopsis - Rugang Yu; Xin Chen; Xinli Pan; Mengru Rong; Lin Yang; Guoliang Wang; Xueling Du (Journal of Plant Biochemistry and Biotechnology, 2026)

Ethylene signaling, pathogenesis-related proteins (PRs) and SlCBF1 collectively regulate Botrytis cinerea resistance in postharvest tomato fruit under low temperature conditions - Pan Shu; Zhiyuan Wang; Bingqing Qian; Zhiyin Yu; Qinlu Zheng; Xin Yao; Hongye Fu; Yuan Qing; Xiaojuan Yin; Pan Zou; Jing Li; Lin Shen (Postharvest Biology and Technology, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Copolymer hydrogel formed by κ-carrageenan and chickpea protein amyloid fibrils: From rheological properties to regulation of aggregation morphology - Lin-Da Zhang; Xiao-Lei Zang; Yu-Nan Pan; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Hydrocolloids, 2026)

In vitro and in vivo evaluation of Bacillus amyloliquefaciens E35 as prophylactic agents against Singapore grouper iridovirus - Yanxia Gao; Lingling Deng; Yibing Wang; Lin Huang; Jieying Yu; Xiangmou Qin; Junxiang Lai; Ermeng Yu; Shuyuan Zhang; Ying Pan; Jiwei Xu; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

A one-tube RAA-PfAgo system for rapid and sensitive detection of Monkeypox virus - Na Zhao; Xuejian Zhang; Yulu Gan; Lin Li; Yunmin Wang; Tong Xu; Yao Pan; Kui Gu; Yu Zhao (Analytica Chimica Acta, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Virus-host metabolic interaction: SGIV-induced protein lactylation suppresses viral propagation - Mingming Zhao; Jiaxi Li; Mingzhu Liu; Ying Pan; Sining Su; Xiangmou Qin; Yanxia Gao; Lin Huang; Junxiang Lai; Jia Cai; Huapu Chen; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Repurposing tumor-derived extracellular vesicles with an adhesive carboxymethyl chitosan-based hydrogel for spinal cord injury repair - Kuan-Lin Wang; Yu-Che Hsiao; Wen-Yu Pan; Chun-Jung Lin; Chieh-Cheng Huang; Yu-Jung Lin (Carbohydrate Polymers, 2026)

Decoupling Risks in the Fringe: An Integrated SOM-PMF Framework for Spatially-Explicit PFAS Source Apportionment Across Surface–Groundwater Interfaces - Xuan Lin; Shengpin Yu; Dandan Huang; Yiwen Pan; Zehui Zhang; Li Zhang; Chunyu Yan; Xiaolu Liu; Bai Gao; Yuanyuan Liu; Wenjie Ma (Water, Air, & Soil Pollution, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

An integrated strategy for Cyclotella cryptica cultivation: From antibiotic selection to efficient mixotrophic bioprocessing - Yalan Yu; Zhichao He; Tengsheng Qiao; Sizhe Fan; Lin Zhang; Jian Li; Spiros N. Agathos; Kehou Pan; Jichang Han (Algal Research, 2026)

Evaluating sustainable coastal management strategies following Spartina alterniflora eradication: Insights from typhoon-induced hydro-sedimentary responses - Lv Gong; Yang Hu; Yuanhao Song; Liangxun Pan; Lin Su; Xiaoyu Yu; Wenzhen Zhao; Ben Li; Xiuzhen Li (Ocean & Coastal Management, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Analysis of the species distribution and drug resistance of pathogenic microorganisms causing diabetic foot infections in Southwest China from 2020 to 2024: a retrospective cross-sectional analysis - Shangyu Zhang; Junchi Chen; Rui Sun; Yu Pan; Yusen Zhuo; Li Tang; Jianhua Zhu; Shuyang Li; Lin Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Preserving the functional integrity of BiP1 is essential for rice storage protein export from the endoplasmic reticulum - Wenkun Yang; Tian Pan; Fan Wang; Yun Zhu; Kunneng Zhou; Binglei Zhang; Gexing Wan; Yu Chen; Yu Zhang; Xiejun Sun; Cailin Lei; Jie Wang; et al. (Plant Science, 2026)

Functional divergence of two ethylene receptor subfamilies in calcium permeability - Chenliang Pan; Junyuan Cheng; Zining Lin; Dongdong Hao; Zhina Xiao; Yuhang Ming; Peng You; Hongtao Yu; Wei Yan; Wen Song; Li Liu; Hongwei Guo (Molecular Plant, 2026)

High-throughput fingerprinting of hydrolysable tannins in wine and oak wood using in-source fragmentation on QTOF and QQQ platforms - Yanxin Lin; Bruce S. Pan; Robert (Qiang) Sui; Ping Yu; Misha T. Kwasniewski (Food Chemistry, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Robigenin in combating largemouth bass ranavirus: Investigating the antiviral potency and underlying mechanisms - Wenyu Liao; Lin Huang; Jieying Yu; Mingzhu Liu; Nijia Xue; Junxiang Lai; Ermeng Yu; Fei Ling; Shuyu Han; Ying Pan; Pengfei Li; Qing Yu (Fish & Shellfish Immunology, 2026)

USP7 protects histone H1.2 from proteasome-mediated degradation to facilitate DNA repair and pancreatic neuroendocrine neoplasms progression - Mujie Ye; Lin Xu; Ping Yu; Jialing Pan; Xiaoting Shi; Bingyan Xue; Na He; Ping Hu; Min Liu; Xintong Lu; Yuemei Xu; Yanling Xu; et al. (Science China Life Sciences, 2026)

Chronic Co-exposure to Environmentally Relevant Concentrations of Cadmium and Glyphosate Exerts Aggravating Nephrotoxicity in Mice - Zhao-Jin Zhong; Kai Chen; Bo Qiu; Pan Chen; Cai-Yu Lian; Lin Wang (Biological Trace Element Research, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Spatiotemporal variability of PAHs and PAEs in sediments driven by hydrological rhythms in Danjiangkou Reservoir, China: Multisource analysis to machine-learning prediction - Li Lin; Lei Dong; Haibo Zhang; Guochuan Yin; Zhuqi Chen; Haiyang Jin; Xingrui Qi; Xiong Pan; Yu Gao (Process Safety and Environmental Protection, 2026)

Recombinant bovine lactoferrin ameliorates cold stress-induced immunosuppression by modulating the gut microbiota in mice - Lin-Lin Ding; Haiyan Sun; Xuan-Yi Xu; Yu Zhang; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Long Pan (Food Bioscience, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Distinction in Symbiodiniaceae and Bacterial Communities and Symbiodiniaceae Lineage‐Specific Transcriptome Underpinning the Superior Heat Tolerance of Intertidal Acropora Corals - Pan Zhang; Lin‐Tao Huang; Xiao‐Lei Yu; Yu‐Yang Zhang; Sheng Liu; Lei Jiang; Hui Huang (Molecular Ecology, 2026)
Fine‐scale thermal heterogeneity within intertidal and subtidal microhabitats could drive divergence in organismal heat tolerance. Reef corals from the extreme intertidal may hold optimism for the future of coral reefs and give insights into the mechanisms by which coral may persist under future conditions. Here, we compared the thermal sensitivities of intertidal and subtidal Acropora digitifera and evaluated their bleaching phenotypes, transcriptomes, host genetic differentiation and bacterial communities. Results showed that only heat‐exposed subtidal corals displayed significantly reduced photochemical efficiency, symbiont densities, pigment and host protein concentrations, suggesting bleaching and host starvation. Despite being genetically similar, heat‐exposed subtidal corals mounted stronger immune activation and amino acid degradation but downregulated monocarboxylate transport and calcification compared to intertidal corals. In contrast to the prevalence of Cladocopium in subtidal corals, intertidal corals were dominated by Durusdinium , whose transcriptional signature was characterised by lineage‐specific and constitutively high transcript abundance of orthologs involved in stress response, metabolism, photosynthesis, cell cycle and symbiotic interactions. Furthermore, 16S rRNA sequencing demonstrated an origin‐dependent bacterial composition, with Endozoicomonas being more abundant and important in co‐occurrence networks of intertidal corals. Our findings suggest that distinction in Symbiodiniaceae and bacterial communities and Symbiodiniaceae lineage‐specific transcriptional footprint largely underpin the exceptional thermotolerance of intertidal Acropora . Although these corals provide promising avenues for restoration, such a mechanism may bring attention to the risk of using them in selective breeding, particularly given the horizontal transmission of algal symbionts in Acropora .

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

From hydrogeochemical genesis to public health risk: Unveiling the links between geogenic arsenic, fluoride, and iodine in groundwater - Furong Yu; Ao Li; Rui Li; Lin Wu; Deng Pan (Journal of Hazardous Materials, 2026)

Dose-dependent root phenotypic plasticity in Casuarina equisetifolia: Mechanistic insights into drought adaptation strategies for coastal sand-fixation afforestation - Chen Fang; Qinqin Lin; Can Chen; Yu Chen; Han Lin; Guoying Pan; Chuanyang Jiang; Anqiang Xie; Xia Li (Journal of Arid Environments, 2026)

Impact of rice protein amyloid fibrils on texture, flavor, digestibility and structural properties of extruded soy protein isolate - Jinming Ma; Deyin Pan; Peng Wang; Xiaoqi Ma; Lin Wang; Mohamed E. Hassan; Xiaoshuai Yu; Baoxin Lu; Zhigang Xiao (Food Research International, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Advancing water and resource recovery from brackish water through electrodialysis-based technologies for circular product ecosystems - Shu-Yuan Pan; Jeremiah Mulia Gianto; Yu-I Lin; Hau-Ming Chang (Desalination, 2026)

Nano-GlycOTAC eradicates Mycobacterium tuberculosis biofilms and rectifies iron metabolism to augment host antimicrobial immunity - Zhuojun He; Deliang Liu; Yang Zhou; Yao Zhao; Guiqin Dai; Zhiqiang Lin; Siwei Zhang; Xiafei Dai; Yuying Chen; Jinzhi Pan; Huiling Liu; Hong Yu; et al. (Chemical Engineering Journal, 2026)

Oriented microstructures and HA/PSP modulation of PEEK implants synergistically promote muscle integration via Myogenesis, immunomodulation and angiogenesis - Yang Su; Yu Chen; Zhengrui Li; Zhaocheng Pan; Lai Jiang; Xiaofeng Xu; Chengshuai Yang; Jinyang Wu; Yong Zhang; Kaili Lin; Shilei Zhang (Chemical Engineering Journal, 2026)

Timing of Antifungal Treatment and Prognostic Factors in Talaromyces marneffei Infection: A Retrospective Analysis of HIV-Positive Cases - Dongzhen Liu; Yusong Lin; Keyao Yu; Zhouhua Xie; Zhipeng Peng; Xinlin Zhu; Haiyang He; Keming Zhang; Weihua Pan (Mycopathologia, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Magnetic resonance imaging for rapid, noninvasive and accurate assessment of ovarian maturation in live Channa argus (Cantor, 1842) - Wenqian Sun; Weiyin Vivian Liu; Xingyu Chen; Guangcan Lin; Hao Li; Yanting Song; Chengdong Peng; Wen Xiong; Yu Peng; Shangong Wu; Shouqi Xie; Sovan Lek; et al. (Aquaculture, 2026)

Integrating multi-stage interventions for harmful algal blooms effective management - Zhuwu Jiang; Jianxin Pan; Chengchun Shi; Xiao Yao; Huang Yu; Junjun Wang; Junjun Chen; Jyunhong Shen; Hai Yu; Wuqiang Zeng; Junlan Chen; Zhihao Lin; et al. (Journal of Environmental Management, 2026)

Unraveling the structure-selectivity nexus: electrode materials for selective phosphorus removal and recovery via capacitive deionization: A systematic review - Sheng Wen; Yu Ma; Yang Fan; Jinxing Lin; Jiaqi Chen; Simiao Li; Huakun Pan; Xinxi Teng; Shupeng Zhang (Chemical Engineering Journal, 2026)

Lactobacillus johnsonii JJB3 Ameliorates Oxidative Stress-Induced Intestinal Injury and Mitochondrial Damage by Promoting BNIP3L-Mediated Mitophagy - Xingmei Liu; Jinge Xin; Ning Sun; Yuhua Qin; Haonan Huang; Benhao Chen; Lixiao Duan; Yanxi Zhou; Dandan Wang; Bo Jing; Yan Zeng; Dong Zeng; et al. (Probiotics and Antimicrobial Proteins, 2026)

Correction: Isolation and functional identification of Jasmonate resistant 1, a jasmonic acid isoleucine-conjugating enzyme in catharanthus roseus - Aikun Pan; Haiqiao Gao; Ying Lin; Bingrun Yang; Chunhao Chang; Zhiwen Liu; Yanyan Wang; Zhaoxia Jin; Fang Yu (Journal of Plant Research, 2026)

Physicochemical properties on the bone of hairtail (Trichiurus lepturus) under various treatments of cooking pressure and vinegar - Huey-Jine Chai; Shang-Ta Wang; Yun-En Chung; Yi-Ting Pan; Yu-Cheng Lin; Wen-Chieh Sung (International Journal of Gastronomy and Food Science, 2025)

Galla Chinensis as an antiviral agent: Targeting Micropterus salmoides rhabdovirus infection - Jieying Yu; Mingzhu Liu; Qing Yu; Xiangmou Qin; Mingming Zhao; Ying Pan; Nijia Xue; Hao Wang; Songlin Li; Fei Ling; Gaoxue Wang; Shuyu Han; et al. (Fish & Shellfish Immunology, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Controlling product selectivity and residual carbon behavior in biomass pyrolysis via pulse-structured joule heating - Yang Liu; Ruming Pan; Renaud Ansart; Chenxu Zhong; Yue Niu; Hongdi Yu; Fawei Lin; Gérald Debenest (Process Safety and Environmental Protection, 2025)

Synergistic effects of biochar and E. coli on reducing cadmium bioavailability and improving soil fertility through enhanced bacterial-fungal interactions - Quan Chen; Rongrong Lin; Wan-Rong Zhang; Yafeng Wang; Yanqing Xiong; Pengfei Wang; Yu Huang; Min Wu; Peng Yi; Bo Pan (Journal of Hazardous Materials, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Geochemical characteristics of Longtan transitional shale gas in the western Hubei Basin, northwest Middle Yangtze Block: Implications for the origin and carbon isotopes - Weiqing Liu; Haiyang Li; Yu Qiao; Wei Wu; Jienan Pan; Chuanlong Mou; Jianxin Yao; Yao Chen; Changsong Lin (Organic Geochemistry, 2025)

Dam operation changed the transport patterns of microplastics - from a global perspective - Yuling Chen; Li Lin; Yi Li; Yu Gao; Lei Dong; Xiong Pan; Ziwei Guo (Environmental Pollution, 2025)

Development of a multifunctional and biocompatible hydrogel for flexible implantable sensors - Kaiqi Zhang; Huibiao You; Yuxi Liu; Fulei Lin; Yanan Li; Lina Jia; Jinxiao Bao; Xin Ge; Gaofei Pan; Huitao Yu; Ruiguang Xing (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

Polarization induced by electric field electro-physically strengthened the proton-coupled electron transfer to promote electrotrophic methanogenesis - Yanwei Liu; Lin Xiao; Zuli Pan; Ouru Zhan; Yabin Gong; Bo Song; Yifeng Shou; Qilin Yu; Yaobin Zhang (Chemical Engineering Journal, 2025)

Isolation and functional identification of Jasmonate resistant 1, a Jasmonic acid isoleucine-conjugating enzyme in Catharanthus roseus - Aikun Pan; Haiqiao Gao; Ying Lin; Bingrun Yang; Chunhao Chang; Zhiwen Liu; Yanyan Wang; Zhaoxia Jin; Fang Yu (Journal of Plant Research, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Plasmonic nanoheater for formaldehyde degassing - Gaopan Chen; Peng Yu; Lian Yang; Roberto Caputo; Feng Lin; Liang Pan; Yang Gao; Hongxing Xu; Alexander Govorov; Zhiming Wang (Chemical Engineering Journal, 2025)

Ionically conductive materials for energy-efficient succinic acid recovery towards electrified circular bioeconomy - Shu-Yuan Pan; Yu-Lun Liao; Yu-I Lin; Po-Chih Tseng (Bioresource Technology, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Polymeric immunoglobulin receptor (pIgR) in cancer progression: a critical role and potential therapeutic target - Shaoju Qian; Yeqing He; Ruixue Li; Panpan Sun; Xingyi Zhang; Lin Pan; Zhishan Xu; Zhiwei Feng; Rong Lian; Lili Yu (Apoptosis, 2025)

Impacts of forest fire on hydro-sediment using the SWAT model: a case study in the Zhangweinan Canal, China - Lin Qi; Xia Li; Yu Pan; Teng Yu (Acta Geophysica, 2025)

Amino-functionalized MIL-101(Fe)-NH2 as efficient peracetic acid activator for selective contaminant degradation: Unraveling the role of electron-donating ligands in Fe(IV) generation - Renjie Pan; Zongchen Li; Tian-Yang Zhang; Qi Fu; Zheng-Xiong Zheng; Jun Shi; Jian Lu; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Journal of Hazardous Materials, 2025)

From water migration to aroma development: Revealing the influence of environmental airflow on the aroma of white tea during withering - Jiao Feng; Shuping Ye; Jinyuan Wang; Junyang Wu; Jiake Zhao; Weisu Tian; Guanjun Pan; Bugui Yu; Dongliang Qiu; Hongzheng Lin; Zhilong Hao (Food Chemistry, 2025)

Reconstructed vanadium carbide MXene supported cerium based trimetallic phosphide as an efficient electrocatalyst for alkaline water splitting - Yu-Han Pan; Sakthivel Perumal; Mani Sakthivel; Shan-Ni Lin; Min-Hsin Yeh; Wen-Yueh Yu; Kuo-Chuan Ho (Chemical Engineering Journal, 2025)

Targeting 5-HT to Alleviate Dose-Limiting Neurotoxicity in Nab-Paclitaxel-Based Chemotherapy - Shuangyue Pan; Yu Cai; Ronghui Liu; Shuting Jiang; Hongyang Zhao; Jiahong Jiang; Zhen Lin; Qian Liu; Hongrui Lu; Shuhui Liang; Weijiao Fan; Xiaochen Chen; et al. (Neuroscience Bulletin, 2025)

Distinct vertical profiles of microbial communities and functional genes between different lake sediment layers mediated by nutrients in the sediments and pore waters - Yu Gao; Bo Zhu; Li Lin; Quanxi Xu; Wei Zhang; Xiong Pan; Lei Dong (Science of The Total Environment, 2025)

Unveiling high-light-use efficiency in Juglans mandshurica: Adaptive insights from leaf morphology and physiology - Qinhui Zhang; Dan Peng; Xiaona Pei; Yitong Chen; Zihan Yan; Mingrui Kang; Jinrong Hu; Yulu Pan; Jingxin Yu; Lu Xu; Huicong Lin; Xiyang Zhao (Forest Ecology and Management, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Cost-effective production of squalene using Yarrowia lipolytica via metabolic engineering and fermentation engineering - Wen-Bo Lin; Hong Chen; Ze-Qi Song; Yu-Qing Pan; Peng-Cheng Hu; Xiao-Na Yang; Xiang-Yang Lu; Yun Tian; Hu-Hu Liu (Biotechnology Letters, 2025)

Interspecific differences in nitrogen form acquisition strategies contribute to species dominance - Ming Guan; Xiao‐Cui Pan; Jian‐Kun Sun; Ji‐Xin Chen; Xiao‐Lin Wei; Bernhard Schmid; Michel Loreau; Yu‐Long Feng (Ecology, 2025)
Plant's ability to use prevalent or less prevalent soil nitrogen (N) forms may affect their dominance within vegetation types, and these partitioning‐driven changes in dominance may facilitate species co‐existence. However, the mechanisms underlying these processes remain unclear, particularly given the strong influence of altitude on soil N forms, which in turn affect plant N acquisition strategy. In this study, we first determined the effects of preference and plasticity in N form uptake on partitioning of soil N forms and species dominance, and then assessed the relative importance of these two N form use strategies for 19 dominant and non‐dominant species in three vegetation types along an altitudinal gradient on Changbai Mountain, northeast China. To achieve this, we measured dominance, the contents of different N forms in rhizosphere soils, their proportional contributions to leaf N, and N form uptake preference and plasticity for these 19 species. Our results show significant interspecific differences in the proportional contributions of different soil N forms to leaf N within all three vegetation types, providing a novel mechanism underlying niche differentiation among plants. Species dominance was positively associated with the proportional contributions of soil dissolved organic N (the most prevalent N form) and the main inorganic N form to leaf N, while negatively with that of the subordinate inorganic N. These associations were not altered by the altitude‐driven changes in the absolute and proportional contents of different soil N forms, suggesting a potentially widespread phenomenon. Both preference and plasticity in N form uptake contributed to the proportional contributions of different N forms to leaf N, and therefore to species dominance and co‐existence within vegetation types. Furthermore, N form preference was more critical for non‐dominant relative to dominant species and at high relative to low altitude, while N form uptake plasticity was more important for dominant species and at low altitude. Our study provides robust evidence for the interspecific niche differentiation in N form uptake, contributing to species dominance and co‐existence within vegetation types, and reveals the mechanisms (plasticity and preference) underlying the association between species dominance and the uptakes of different N forms.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Efficient removal of tetracycline under neutral pH using FeOCl-modified carbon-based catalytic membrane via in-situ coupling fenton oxidation - Zonglin Pan; Xinyuan Zhou; Xinyu Liu; Chengwen Song; Wei Qian; Hang Yu; Ruisong Xu; Lin Li; Shuaifei Zhao; Tonghua Wang (Journal of Water Process Engineering, 2025)

Exploring Potential Health Risk of Chenxiang Huaqi Tablets Based on Inorganic Elemental Evaluation Using ICP-MS - Shuxiang Pan; Lin Yang; Yiwu Wang; Yuan Shen; Jialing Yu; Dan He (Biological Trace Element Research, 2025)

Development of a rat airway organoids model for studying chronic obstructive pulmonary disease - Chuanlai Yang; Hongwei Yang; Yangling Xian; Nanyi Liu; Haoyin Tan; Zirui Ren; Yanzhen Lin; Huan Zhao; Changjian Fang; Kang Yu; Dequan Pan; Yali Zhang; et al. (Tissue and Cell, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

Nano Sim@ZIF8@PDA modified injectable temperature sensitive nanocomposite hydrogel for photothermal/drug therapy for peri-implantitis - Dingkun Liu; Jinbing Chen; Linjuan Gao; Xing Chen; Liujun Lin; Yuan Liu; Xia Wei; Yu Pan; Yinghui Wang; Hui Cheng (Carbohydrate Polymers, 2025)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Di-Wei Ma; Khalid Hassan Mohamed; Jian-Lin Hu; Chang-Qin Yin; Yu-Bin Wei; Xiao-Pan Chai; Qing-Bao Zhang; Lan-Chun Zhang; Jia Liu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2025)

Environmental Factors Influencing Groundwater Quality and Health Risks in Northern Henan Plain, China - Yu Ren; Wengeng Cao; Lihua Zhao; Shuai Wang; Deng Pan; Lin Zhang; Xiangzhi Li; Shunyu Xiao; Zeyan Li (Exposure and Health, 2025)

Polyploid crape myrtle was produced through hybridizing with 2n gametes induced by high-temperature - Yu Xu; Qi Hu; Qifang Lin; Xiufeng Chi; Ping Shen; Xin Wang; Zhiting Wan; Xinwei Jiang; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

Allopatric Speciation and Interspecific Gene Flow Driven by Niche Conservatism of Diploderma Tree Lizards in Taiwan - Tzong‐Han Lin; Zong‐Yu Shen; Ming‐Hsun Chou; Pei‐Wei Sun; Chin‐Chia Shen; Jen‐Pan Huang; Si‐Min Lin (Molecular Ecology, 2025)
Allopatric speciation is a widely accepted hypothesis for species distributed across geographic barriers. Meanwhile, niche conservatism, the tendency of species to retain their ancestral ecological traits, helps reinforce genetic differentiation by stabilising species distributions over time and reducing the role of competition in shaping range boundaries. In contrast, hybridisation can occur at the edges of distribution after secondary contact following climatic or geological events, leading to a reduction in genetic divergence between divergent lineages. In this study, we investigated the role of geographic barriers, niche conservatism and gene flow in the speciation history of Diploderma species in Taiwan, where geographically distinct taxa share similar environmental preferences. By using ddRAD‐seq data, seven distinct genetic clusters were identified with two putatively new cryptic species in D. brevipes and D. polygonatum . Most sister species pairs share similar climatic niches based on niche equivalency and similarity tests. We further detected significant historical gene flow between lineages of D. brevipes and D. polygonatum , where secondary contact might have occurred because of palaeoclimate changes and historical demographic expansion. Our results demonstrate that niche conservatism does not always act in concert to strengthen the result of allopatric speciation; instead, it may also lead to gene flow between divergent lineages following secondary contact. On the other hand, postdivergence gene flow may be a creating force generating phenotypic diversity in sexually selected traits in our study system. The underestimated species diversity of Diploderma in Taiwan requires further taxonomic work in the future.

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Effects of mixed exposure to PFAS on adolescent non-alcoholic fatty liver disease: Integrating evidence from human cohorts, toxicogenomics, and animal models to uncover mechanisms and potential target sites - Xiushuai Du; Dan-Lin Li; Xueming Xu; Yitian Wu; Zhiyuan Du; Gang Liang; Yue-Zu Li; Ya-Jie Zheng; Yu Qin; Kelei Qian; Jing Xu; Liping Gao; et al. (Journal of Hazardous Materials, 2025)

MnOOH/carbon-based reactive electrochemical membrane for aqueous organic pollutants decontamination - Zonglin Pan; Chunyu Wang; Xinyu Liu; Ruisong Xu; Hong Xin; Hang Yu; Lin Li; Shuaifei Zhao; Chengwen Song; Tonghua Wang (Journal of Environmental Management, 2025)

A study on the impact of meteorological and emission factors on PM2.5 concentrations based on machine learning - Chenxu Zhao; Zejian Lin; Leifeng Yang; Mengmeng Jiang; Zhubing Qiu; Siyu Wang; Yu Gu; Wei Ye; Yusuo Pan; Yong Zhang; Tianxin Wang; Yong Jia; et al. (Journal of Environmental Management, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Synthesis of phosphorylated covalent organic frameworks with different linkages–Critical factors controlling the extraction of uranium from highly acidic media - Xiao-Yi Tang; Hui-Di Zhang; Zi-Jie Li; Shuai Wang; Si-Yan Liu; Tao-Yuan Xiu; Ji-Pan Yu; Lin Wang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Hydrogel-filled micropipette enables antifouling in vivo iontronic sensing - Guangguo Guo; Yifei Pan; Tianyi Xiong; Wenliang Ji; Wenjie Ma; Ping Yu; Yuqing Lin; Lanqun Mao (Science Bulletin, 2025)

Characteristics, sources, and concentration prediction of endocrine disruptors in a large reservoir driven by hydrological rhythms: A case study of the Danjiangkou Reservoir - Lei Dong; Xingrui Qi; Li Lin; Kefeng Zhao; Guochuan Yin; Liangyuan Zhao; Xiong Pan; Zhiguang Wu; Yu Gao (Journal of Hazardous Materials, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Enhancing porcine oocyte quality and embryo development through natural antioxidants - Zheng Feng; Jia Song; Chenghong Lin; Siyu Wu; Yu Wang; Qingyuan Hui; Yinting Pan; Yiman Zou; Chaofeng Zeng; Jinbiao Guo; Yangli Pei (Theriogenology, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

Detection of Tetracycline in Farm Wastewater by Nitrogen-doped Carbon Quantum Dots - Peilan Yu; Lintong Ji; Teng Wang; Juan Hu; Lihao Jiang; Shancai Guo; Yongjian Pan; Jianyuan Lin (Journal of Fluorescence, 2024)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Egg production monitoring in commercial laying cages via the StrongSort-EGG tracking-by-detection model - Rui Wu; Pengguang He; Yefan He; Jun Dou; Mengzui Di; Shupeng He; Khawar Hayat; Yi Zhou; Lin Yu; Jinming Pan; Hongjian Lin (Computers and Electronics in Agriculture, 2024)

Community prevention and standardized clinical treatment jointly improve cancer outcome: Real-world evidence from an esophageal cancer patient cohort study - Ji Ke; Fangfang Liu; Wei Yang; Ruiping Xu; Lei Chen; Wenlei Yang; Yu He; Zhen Liu; Bolin Hou; Liqun Zhang; Miaoping Lin; Lixin Zhang; et al. (Science Bulletin, 2024)

The zinc-finger transcription factor ZFP8 negatively regulates the drought stress response in Arabidopsis thaliana by inhibiting the transcriptional activity of ABF2 - Yu'ang Tian; Yanling Li; Kelan Wang; Ran Xia; Yingru Lin; Guohui Pan; Haoyu Shi; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2024)

Performance evaluation of resin wafer electrodeionization for enhanced nitrogen recovery from ammonium-containing water environment - Redae Nuguse Berhe; Yu-I Lin; Shu-Yuan Pan; Min Zhan; Hyunook Kim (Chemical Engineering Journal, 2024)

The association of air pollution with blood pressure, heart rate and stress among office workers using essential oils - Chien-Yu Lee; I-Jung Liu; Chih-Hong Pan; Lian-Yu Lin; Hsiao-Chi Chuang; Kin-Fai Ho; Chia-Huang Chang; Kai-Jen Chuang (Atmospheric Environment, 2024)

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

Coordinated measurement of marine economy: High-quality and low-carbon development in China - Lin Pan; Qingwu Meng; Zhiwen Wang; Jiale Wu; Jing Yu (Ocean & Coastal Management, 2024)

Synergistic effects of metallic IrCo for promoted nitrate reduction in industrial-relevant wastewater level - Yu Tang; Pan Ran; Linjun Zhong; Haohong Liao; Qing Tong; Weixin Zou; Lin Dong (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Molecular characterization of histone gene in golden pompano (Trachinotus ovatus) and antimicrobial activity of its derived peptides - Yu Liang; Jin-Min Pan; Ke-Cheng Zhu; Lin Xian; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Teng-Fei Zhu; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

Local adaptation of trophic strategy determined the tolerance of coral Galaxea fascicularis to environmental fluctuations - Xiao-Lei Yu; Cheng-Yue Liu; Lei Jiang; Lin-Tao Huang; Yong Luo; Pan Zhang; Yu-Yang Zhang; Sheng Liu; Hui Huang (Science of The Total Environment, 2024)

Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2024)

A down-regulated cytochrome P450 in Neoseiulus barkeri Hughes (Acari: Phytoseiidae) can dechlorinate and hydroxylate chlorpyrifos without producing chlorpyrifos-oxon - Shi-Jiang Yu; Li Wang; Li-Li Ding; Qi Pan; Si-Chen Li; Liu Liu; Lin Cong; Chun Ran (Journal of Hazardous Materials, 2024)

Insights into the impact of metals in waste activated sludge on its anaerobic digestion: From perspectives of physical structure and organic matter composition - Yu Zhang; Shushan Hu; Jinze Li; Yifei Wang; Miao Liu; Haoyang Li; Lin Li; Li Gu; Weiliang Pan; Qiang He (Fuel, 2024)

An integrated approach to optimizing concentration shock wave electrodialysis using 2D multicell simulation and response surface models - Yu-I Lin; Shu-Yuan Pan; Yupo J. Lin; Po-Chih Tseng (Chemical Engineering Journal, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Screening and identification of reactive metabolic compounds of Cortex Periplocae based on glutathione capture-mass spectrometry - Guantong Yu; Ruirui Wang; Xiaomei Liu; Yuhong Li; Lin Li; Xiaoming Wang; Yuhong Huang; Guixiang Pan (Journal of Natural Medicines, 2024)

Enhancing lithium extraction from low grade salt lake brines using high powder loading aluminum-based adsorbent granules - Yanan Pan; Ye Zhang; Haiping Su; Jianguo Yu; Sen Lin (Desalination, 2024)

Single nucleotide polymorphisms reveal the uniqueness of Gushan semi-rock tea in the tea germplasm resources of Fujian, China - Pan Wang; Shuiyuan Lv; Wentao Yu; Cheng Lin; Yanyu Zhu; Wenjing Gui; Caiguo Liu; Naixing Ye (Genetic Resources and Crop Evolution, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Innovative treatment of industrial effluents through combining ferric iron and attapulgite application - Zhenxiang Pan; Bizhen Zeng; Liguo Shen; Jiaheng Teng; Tongli Lai; Leihong Zhao; Genying Yu; Hongjun Lin (Chemosphere, 2024)

Electroneutralization desalination with spontaneous chemoelectric power generation - Aishwarya Rani; Shu-Yuan Pan; Suraj Negi; Yu-I Lin (Water Research, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Axisymmetric finite strain consolidation model for soft soil consolidation with vertical drains under combined loading considering creep and non-Darcy flow - Peng-Lin Li; Zhen-Yu Yin; Ding-Bao Song; Jian-Hua Yin; Yu Pan (Geotextiles and Geomembranes, 2024)

Identification and function analysis of BCL2 in immune response of Pteria penguin - Wenhao He; Jinji Lin; Feifei Yu; Yang Leng; Zhenni Pan; Qiwen Liang; Siying Liu; Xinyue Huang (Fish & Shellfish Immunology, 2024)

Cell-derived biomimetic nanoparticles for the targeted therapy of ALI/ARDS - Rui Gao; Peihong Lin; Zhengyu Fang; Wenjing Yang; Wenyan Gao; Fangqian Wang; Xuwang Pan; Wenying Yu (Drug Delivery and Translational Research, 2024)

Protective effect of resveratrol on nickel-refining fumes-induced inflammatory damage - Yu-Lin Pan; Rui-Ze Wu; Yao Fu; Rui Xin; Yong-Hui Wu (Cell Biochemistry and Biophysics, 2024)

Correction: Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)

The effects of turbulence on the growth of three different diatom species - Yijing Liu; Lin Yu; Zhongzhi Yao; Yunwen Shen; Yiwen Pan (Frontiers in Marine Science, 2024)
The effects of turbulence on phytoplankton growth have received considerable attentions. However, the complexity of turbulence poses a significant challenge to its systematic characterization in the laboratory, resulting in relatively limited data on the effects of turbulence on several algal species. Here, a laboratory turbulence simulation system was set up to systematically investigate the growth of three common diatom species ( Thalassiosira pseudonana, Skeletonema costatum , and Phaeodactylum tricornutum ) under stationary and turbulent conditions (at 60, 120, 180 rpm), and measurements were taken for the algal biomass, algal photosynthetic activity, and nutrients consumption. By comparing the growth of three algae species under different turbulence exposure intensities, this study found that different algae exhibit varying sensitivities to turbulence, and therefore have different shear thresholds. Meanwhile, cell morphology is the key factor influencing the different shear threshold values observed in the three diatom species. Additionally, turbulence could impact algal aggregation and light availability, and dramatically improve nutrient uptake by phytoplankton. Our study will provides theoretical support for future endeavors in using turbulence to cultivate phytoplankton or combat algal blooms.

Rh/InGaN1−O nanoarchitecture for light-driven methane reforming with carbon dioxide toward syngas - Yixin Li; Jinglin Li; Tianqi Yu; Liang Qiu; Syed M. Najib Hasan; Lin Yao; Hu Pan; Shamsul Arafin; Sharif Md. Sadaf; Lei Zhu; Baowen Zhou (Science Bulletin, 2024)

Urchin-like CO2-responsive magnetic microspheres for highly efficient organic dye removal - Lin Yang; Yongxiang Sun; Ruiquan Yu; Pan Huang; Qi Zhou; Haoyu Yang; Shaojian Lin; Hongbo Zeng (Journal of Hazardous Materials, 2024)

Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)
Bacteria with functional DNA repair systems are expected to have low mutation rates due to strong natural selection for genomic stability. However, our study of the wild-type Streptococcus pneumoniae D39, a pathogen responsible for many common diseases, revealed a high spontaneous mutation rate of 0.02 per genome per cell division in mutation-accumulation (MA) lines. This rate is orders of magnitude higher than that of other non-mutator bacteria and is characterized by a high mutation bias in the A/T direction. The high mutation rate may have resulted from a reduction in the overall efficiency of selection, conferred by the tiny effective population size in nature. In line with this, S. pneumoniae D39 also exhibited the lowest DNA mismatch-repair (MMR) efficiency among bacteria. Treatment with the antibiotic penicillin did not elevate the mutation rate, as penicillin did not induce DNA damage and S. pneumoniae lacks a stress response pathway. Our findings suggested that the MA results are applicable to within-host scenarios and provide insights into pathogen evolution.

Life-stage specificity and temporal variations in transcriptomes and DNA methylomes of the reef coral Pocillopora damicornis in response to thermal acclimation - Lei Jiang; Pan Zhang; Lin-Tao Huang; Xiao-Lei Yu; Cheng-Yue Liu; Xiang-Cheng Yuan; Sheng Liu; Hui Huang (Science of The Total Environment, 2024)

Development and evaluation of an online monitoring single-particle optical particle counter with polarization detection - Weijie Yao; Xiaole Pan; Yu Tian; Hang Liu; Yuting Zhang; Shandong Lei; Junbo Zhang; Yinzhou Zhang; Lin Wu; Yele Sun; Zifa Wang (Journal of Environmental Sciences, 2024)

Heteroatom doping-induced Pt dispersion and electronic effect for boosting the catalytic performance in the hydrogenation of nitrobenzene to p-aminophenol - Chong Yao; Jiwei Wu; Limei Pan; Lu Yu; Jie Luo; Jinjin Shan; Jie Liu; Chunshan Lu; Feng Feng; Xiaoliang Xu; Lili Lin; Yuxue Yue; et al. (Chemical Engineering Journal, 2024)

Performance boosting by induction heating for hydrolysis of carbonyl sulfide using magnetic ordered mesoporous alumina as catalyst - Chao Huang; Yunchuan Hong; Binchen Wu; Hongchao Yu; Xiangqian Du; Min Pan; Weiyi Fan; Fei Gao; Feng Wu; Yixin Zhong; Lin Li; Guoshu Deng; et al. (Chemical Engineering Journal, 2024)

Metal-phenolic nanocatalyst rewires metabolic vulnerability for catalytically amplified ferroptosis - Yang Zhu; Xuegang Niu; Tiantian Wu; Junjie Cheng; Jianhua Zou; Yuanbo Pan; Yu Tian; Wei Huang; Chengyu Ding; Yuanxiang Lin; Dezhi Kang; Xiaoyuan Chen (Chemical Engineering Journal, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Spawning, larval morphological ontogeny and first feeding of yellow-striped cardinalfish Ostorhinchus cyanosoma (Bleeker, 1853) - Ang Lu; Xiang-Yu Li; Yi-Yang Lin; Yen-Ju Pan (Aquaculture, 2024)

Reduction of antigenicity and emulsibility improvement of ovalbumin by dielectric-barrier discharge plasma treatment induced structure modification - Pan-Pan Tang; Lin-Lin Zhang; Yu-Xin Xiong; Dan-Dan Jiang; Xiu-Bin Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Zhi-Wei Liu (Innovative Food Science & Emerging Technologies, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Identification of key factors affecting neonicotinoid residues in crops and risk of dietary exposure - Wenfei Yu; Ruxin Wu; Li Zhang; Yangzhong Pan; Jun Ling; Dan Yang; Jiajia Qu; Zhen Tao; Ruirui Meng; Yuexing Shen; Jingtong Yu; Nan Lin; et al. (Environmental Pollution, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Prevalence and distribution of antibiotic-resistant bacteria in the rhizosphere and rhizoplane of Suaeda salsa and Sporobolus alterniflorus grown in a pristine environment - Yu Wang; Fang Yang; Qianwen Liu; Lin Sun; Weihua Chen; Qingfeng Yu; Chenglong Pan; Guanhong Jiang; Xin'an Jiao; Yunzeng Zhang (Applied Soil Ecology, 2024)

Cancer screening in hospitalized ischemic stroke patients: a multicenter study focused on multiparametric analysis to improve management of occult cancers - Jie Fang; Jielong Wu; Ganji Hong; Liangcheng Zheng; Lu Yu; Xiuping Liu; Pan Lin; Zhenzhen Yu; Dan Chen; Qing Lin; Chuya Jing; Qiuhong Zhang; et al. (EPMA Journal, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Comparison of four pre-oxidants coupled powdered activated carbon adsorption for odor compounds and algae removal: Kinetics, process optimization, and formation of disinfection byproducts - Heng-Xuan Zhao; Shuang Zhang; Tian-Yang Zhang; Yi-Ping Zhu; Ren-Jie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Science of The Total Environment, 2024)

Preparation and 3D printing of high internal-phase Pickering emulsions stabilized by chicken egg white microgel - Xiliang Yu; Lin Han; Jiaqi Liu; Wenjia Jiang; Jinfeng Pan; Chenxu Yu; Xiuping Dong (Food Hydrocolloids, 2024)

Mitigation of multiple outliers using consistency checking for GNSS standard point positioning in urban areas - Yaxin Wen; Wujiao Dai; Wenkun Yu; Lin Pan (Advances in Space Research, 2024)

Protection of Pacific white shrimp (Penaeus vannamei) against white spot syndrome virus infection by nitric oxide-generating compound S-nitrosoglutathione - Qingna Lai; Chen Yu; Furong Zhao; Yunying Cheng; Qin Zheng; Changkun Pan; ZhenYue Lin; Suping Yang; Qian Zhang; Jianming Chen; Wei Wang (Aquaculture, 2024)

Group VIII metal difluorocarbene complexes: Synthesis and applications - Xue Ding; Yu-Fei Yao; Weikang Lin; Zhengqing Ye; Cheng-Pan Zhang (Journal of Fluorine Chemistry, 2024)

Lineaperpetua gen. nov.: a new diatom genus in the Thalassiosirales supported by morphology and molecular data - Pan Yu; Lin Yang; Qingmin You; John Patrick Kociolek; Kangyu Wang; Yonghong Bi; Quanxi Wang (Journal of Oceanology and Limnology, 2024)

Mixed chlorine/chloramines in disinfected water and drinking water distribution systems (DWDSs): A critical review - Renjie Pan; Tian-Yang Zhang; Huan He; Zheng-Xiong Zheng; Zheng-Yu Dong; Heng-Xuan Zhao; Meng-Yuan Xu; Zhen-Ning Luo; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Water Research, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

Enhanced resuscitation of anammox granular sludge by adding folate: A perspective from the growth factor - Chao Pan; Leiyan Guo; Yang Yu; Wenji Li; Dongdong Xu; Wenda Chen; Lin Zhu; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Identification and validation of key biomarkers and potential therapeutic targets for primary open-angle glaucoma - Jian Wu; Caixia Lin; Chenlong Yang; Lijie Pan; Hongyi Liu; Sirui Zhu; Shuwen Wei; Xu Jia; Qi Zhang; Ziyu Yu; Xiaofang Zhao; Weihai Liu; et al. (Science China Life Sciences, 2023)

STAT6 promoting oxalate crystal deposition-induced renal fibrosis by mediating macrophage-to-myofibroblast transition via inhibiting fatty acid oxidation - Tianhui Yuan; Yuqi Xia; Shengyu Pan; Bojun Li; Zehua Ye; Xinzhou Yan; Weimin Hu; Lei Li; Baofeng Song; Weimin Yu; Haoyong Li; Ting Rao; et al. (Inflammation Research, 2023)

The cellular trajectories of tumor-associated macrophages decipher the heterogeneity of pancreatic cancer - Jiajing Lin; Fengchun Lu; Yuwei Wu; Heguang Huang; Yu Pan (Functional & Integrative Genomics, 2023)

Role of feeding and physiological trade-offs in sustaining resilience of the coral Galaxea fascicularis to light limitation - Xiao-Lei Yu; Lei Jiang; Yong Luo; Cheng-Yue Liu; Yu-Yang Zhang; Lin-Tao Huang; Pan Zhang; Xiang-Cheng Yuan; Hui Huang (Coral Reefs, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Carrageenan addition improves the melting temperature and 3D printing performance of the gelatin system - Yue Wang; Lin Han; Wanying Yu; Weiping Zhao; Jinfeng Pan; Sangeeta Prakash; Xiuping Dong (Food Hydrocolloids, 2023)

Electroneutralization with simultaneous highly-efficient desalination exemplified by acidic brackish wastewater - Yu-I Lin; Shu-Yuan Pan (Chemical Engineering Journal, 2023)

High-rate GNSS multi-frequency uncombined PPP-AR for dynamic deformation monitoring - Lin Pan; Bowen Xiong; Xuanping Li; Wenkun Yu; Wujiao Dai (Advances in Space Research, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Design, synthesis, and biological activity of 9- O -cinnamoylberberines as novel lipid-lowering agents - Yuan Kong; Qi-Qi Xing; Yu-Xuan Tian; Lin Li; Pan Yu; Lin-Guo Zhao; Dong-Dong Li (Natural Product Research, 2023)

Using drone soundings to study the impacts and compositions of plumes from a gigantic coal-fired power plant - Yen-Chen Chen; Jia-Lin Wang; Chih-Yuan Chang; Ming-Tung Chuang; Charles C.-K. Chou; Xiang-Xu Pan; Yu-Jui Ho; Chang-Feng Ou-Yang; Wen-Tzu Liu; Chih-Chung Chang (Science of The Total Environment, 2023)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

Contribution of the SOS response and the DNA repair systems to norfloxacin induced mutations in E. coli - Tongtong Lin; Jiao Pan; Colin Gregory; Yaohai Wang; Clayton Tincher; Caitlyn Rivera; Michael Lynch; Hongan Long; Yu Zhang (Marine Life Science & Technology, 2023)
Antibiotic-resistant bacteria severely threaten human health. Besides spontaneous mutations generated by endogenous factors, the resistance might also originate from mutations induced by certain antibiotics, such as the fluoroquinolones. Such antibiotics increase the genome-wide mutation rate by introducing replication errors from the SOS response pathway or decreasing the efficiency of the DNA repair systems. However, the relative contributions of these molecular mechanisms remain unclear, hindering understanding of the generation of resistant pathogens. Here, using newly-accumulated mutations of wild-type and SOS-uninducible Escherichia coli strains, as well as those of the strains deficient for the mismatch repair (MMR) and the oxidative damage repair pathways, we find that the SOS response is the major mutagenesis contributor in mutation elevation, responsible for ~ 30–50% of the total base-pair substitution (BPS) mutation-rate elevation upon treatment with sublethal levels of norfloxacin (0 ~ 50 ng/mL). We further estimate the significance of the effects on other mutational features of these mechanisms (i.e., transversions, structural variations, and mutation spectrum) in E. coli using linear models. The SOS response plays a positive role in all three mutational features (mutation rates of BPSs, transversions, structural variations) and affects the mutational spectrum. The repair systems significantly reduce the BPS mutation rate and the transversion rate, regardless of whether antibiotics are present, while significantly increasing the structural variation rate in E. coli . Our results quantitatively disentangle the contributions of the SOS response and DNA repair systems in antibiotic-induced mutagenesis.

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Enhanced biomethane production with a low carbon footprint via anaerobic co-digestion of swine wastewater with rice husk - Hung-Cheng Lin; Shu-Yuan Pan; Yu-I Lin; Dan-Thanh Ngoc Cao (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Estimating the daily average concentration variations of PCDD/Fs in Taiwan using a novel Geo-AI based ensemble mixed spatial model - Chin-Yu Hsu; Tien-Wei Lin; Jennieveive B. Babaan; Aji Kusumaning Asri; Pei-Yi Wong; Kai-Hsien Chi; Tuan Hung Ngo; Yu-Hsuan Yang; Wen-Chi Pan; Chih-Da Wu (Journal of Hazardous Materials, 2023)

Sublethal effects of methylmercury on lateral line sensory and ion-regulatory functions in zebrafish embryos - Giun-Yi Hung; Yu-Chin Pan; Jiun-Lin Horng; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Simvastatin-enhanced bioinspired exosome mimetics regulate osteogenesis and angiogenesis for the treatment of glucocorticoid-induced osteonecrosis of the femoral head - Hongyi Jiang; Chao Lou; Liting Jiang; Chihao Lin; Weidan Wang; Zijian Yan; Jiachen Yu; Tingwen Cai; Shida Lin; Jilong Wang; Xiaoyun Pan; Xinghe Xue (Chemical Engineering Journal, 2023)

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

Effects of biochar supported nano zero-valent iron with different carbon/iron ratios on two-phase anaerobic digestion of food waste - Pan Wang; Miao Yu; Peiru Lin; Yi Zheng; Lianhai Ren (Bioresource Technology, 2023)

Seed traits of reintroduced invasive populations of Triadica sebifera show few differences in comparison with those of native populations - Yu-Lin Li; Yun-Tao Xiong; Jie-Ren Jin; Chao-Nan Wang; Zhi-Li Pan; Jie Wang; Yan Wang; Yi Wang (Plant Ecology, 2023)

Insight into mixed chlorine/chloramines conversion and associated water quality variability in drinking water distribution systems - Renjie Pan; Tian-Yang Zhang; Zheng-Xiong Zheng; Jian Ai; Tao Ye; Heng-Xuan Zhao; Chen-Yan Hu; Yu-Lin Tang; Jing-Jing Fan; Bing Geng; Bin Xu (Science of The Total Environment, 2023)

Swc4 protects nucleosome-free rDNA, tDNA and telomere loci to inhibit genome instability - Yue Pan; Can Hu; Lin-Jun Hou; Yu-Long Chen; Jiantao Shi; Jia-Cheng Liu; Jin-Qiu Zhou (DNA Repair, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

The interspecific competition of tree plants in the presence of AM fungi and litter facilitates root morphological development and nutrition when compared with intraspecific competition - Yun Guo; Kaiping Shen; Tingting Xia; Yuejun He; Wenda Ren; Pan Wu; Yan Lin; Bangli Wu; Xu Han; Lu Gao; Jinting Li; Xiaorun Hu; et al. (Environmental Science and Pollution Research, 2023)

Hydrogen sulfide antagonizes formaldehyde-induced ferroptosis via preventing ferritinophagy by upregulation of GDF11 in HT22 cells - Yu-Hui Tang; Lei Wu; Hong-Lin Huang; Pan-Pan Zhang; Wei Zou; Xiao-Qing Tang; Yi-Yun Tang (Toxicology, 2023)

Cartilage-targeting mRNA-lipid nanoparticles rescue perifocal apoptotic chondrocytes for integrative cartilage repair - Xinning Yu; Tengjing Xu; Huimin Shi; Jianqiao Hong; Xiaoqiang Jin; Le Cao; Jiajie Wang; Yunting Lin; Zongyou Pan; Siheng Wang; Jinghua Fang; Kaiwang Xu; et al. (Chemical Engineering Journal, 2023)

Kungurian sedimentary environments in the slope facies of the Xuyong area, South China, and a comparative analysis of low-latitude palaeogeography - Liangjun Wu; Haixian Jiang; Ming Pan; Pujun Wang; Jingsong Hu; Jiwen Wu; Yu Lin; Wenqiang Shi (Carbonates and Evaporites, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Performance of 3D-printed samples based on starch treated by radio frequency energy - Shu Ma; Qianru Zhang; Qian Lin; Lin Pan; Xiuzhu Yu; Hao Jiang (Innovative Food Science & Emerging Technologies, 2023)

Structural, mechanical and thermal properties of cubic bixbyite-structured high-entropy oxides - Xinyu Ping; Bin Meng; Xiaohua Yu; Zhiyuan Ma; Xiaoyu Pan; Wu Lin (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Ambient temperature and nervous system diseases-related mortality in Japan from 2010 to 2019: A time-stratified case-crossover analysis - Szu Yu Lin; Chris Fook Sheng Ng; Yoonhee Kim; Zin Wai Htay; Alton Quan Cao; Rui Pan; Masahiro Hashizume (Science of The Total Environment, 2023)

Polystyrene microplastics arrest skeletal growth in puberty through accelerating osteoblast senescence - Chun Pan; Yin Wu; Sihan Hu; Ke Li; Xiangyu Liu; Yu Shi; Wenzheng Lin; Xinglong Wang; Yujie Shi; Zhuobin Xu; Huihui Wang; Hao Chen (Environmental Pollution, 2023)

Eicosane-based thermo-conductive phase change composite for efficient capture solar energy and using in real-environment as power source - Linhong Li; Maohua Li; Yue Qin; Yapeng Chen; Wen Dai; Zhenbang Zhang; Xiangdong Kong; Ping Gong; Yandong Wang; Rongjie Yang; Bo Wang; Tao Cai; et al. (Chemical Engineering Journal, 2023)

Unveiling the effect of structural water on Zn-ion storage of polyoxovanadate for high-rate and long-life aqueous zinc ion battery - Huan He; Fu-Chun Pan; Xue-Wei Liang; Qiang Hu; Shude Liu; Jisong Hu; Seong Chan Jun; Dunmin Lin; Yusuke Yamauchi; Yu Huo (Chemical Engineering Journal, 2023)

PanGu Drug Model: learn a molecule like a human - Xinyuan Lin; Chi Xu; Zhaoping Xiong; Xinfeng Zhang; Ningxi Ni; Bolin Ni; Jianlong Chang; Ruiqing Pan; Zidong Wang; Fan Yu; Qi Tian; Hualiang Jiang; et al. (Science China Life Sciences, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Sequential combination of pre-chlorination and powdered activated carbon adsorption on iodine removal and I-THMs control in drinking water - Renjie Pan; Yi-Li Lin; Tian-Yang Zhang; Xiu-Li Wei; Zheng-Yu Dong; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Chemosphere, 2023)

Modeling of an integrated H2S/NH3 scrubber and regeneration columns for coke oven gas purification - Hao-Jen Pan; Ming-Chun Fang; Jeffrey D. Ward; Hao-Yeh Lee; Hsun-Yu Lin; Cheng-Ting Hsieh; Chih-Lung Lee; Tzu-Hsien Huang; Yu-Chen Hsieh; Shih-Chieh Lin; Wei-Ti Chou (Journal of Cleaner Production, 2023)

WSV056-mediated downregulation of PvSMCT1 contributes to immune evasion of white spot syndrome virus in the infection of Penaeus vannamei - Wei Wang; Jinlin Chen; Chen Yu; Changkun Pan; ZhenYue Lin; Jianming Chen (Aquaculture, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Effect of confining pressure on the fracture mechanical properties of multi-particle sandstone - Kai-wen Shi; Yu-jun Zuo; Wenjibin Sun; Hao Liu; Chao Pan; Taotao Li; Bin Chen; Jian-yun Lin (Arabian Journal of Geosciences, 2022)

Plant secondary metabolite and temperature determine the prevalence of Arsenophonus endosymbionts in aphid populations - Chun‐Yan Chang; Xiao‐Wan Sun; Pan‐Pan Tian; Ning‐Hui Miao; Yu‐Lin Zhang; Xiang‐Dong Liu (Environmental Microbiology, 2022)
Summary Transmission rate and role in hosts contribute to the prevalence of an endosymbiont. However, factors affecting transmission and role of facultative endosymbionts are still not well understood. Here, we illustrated that host plants and environmental temperatures affected the transmission, relative abundance and role of Arsenophonus in the cotton aphid Aphis gossypii . The transmission rate of this endosymbiont from mother aphids to offspring was relatively lower. High temperatures impeded the transmission, and infection rates declined as aphids were exposed to 30°C. Contents of amino acids and secondary metabolites were remarkably different among host plants. Aphids feeding on zucchini leaves containing a higher titre of amino acids and lower secondary metabolites harboured a relatively lower abundance of Arsenophonus . Concentrations of an amino acid and a plant secondary metabolite, cucurbitacin B, in aphid diet were not associated with Arsenophonus abundance. However, gossypol, another plant secondary metabolite, was strongly related with the abundance. Arsenophonus imparted a fitness benefit to aphids, and the benefit was dependent on host plants and gossypol concentration. In sum, plant secondary metabolite and environmental temperature affect transmission, relative abundance and role of Arsenophonus , which determine the endosymbiont prevalence in aphid populations.

Characterization of Fine-Scale Turbulence Generated in a Laboratory Orbital Shaker and Its Influence on Skeletonema costatum - Lin Yu; Yifan Li; Zhongzhi Yao; Long You; Zong-Pei Jiang; Wei Fan; Yiwen Pan (Journal of Marine Science and Engineering, 2022)
Turbulence is one of the ubiquitous aspects of aquatic systems and affects many physical and biological processes. Based on direct velocity measurements and a computational fluid dynamics (CFD) simulation, we characterized the distribution of the turbulent kinetic dissipations rates (ε) in an orbital shaker system within a range of rotation frequencies. CFD was able to estimate the ε distribution in containers accurately, which was confirmed by other two methods and was independent of velocity measurement. The results showed that ε was linearly correlated with the rotational frequencies. Despite the existence of gradients of ε and the fact that a mean circular horizontal flow was formed within the tank, the energy levels of the whole tank varied spatially within an order of magnitude and the ε distributions at different rotational frequencies were similar, suggesting that the ε distribution in the whole tank could be seen as quasi-homogeneous. To investigate the influence of turbulence on algae growth, culture experiments of a typical diatom—Skeletonema costatum were carried out under different turbulence conditions. Our results suggested turbulence mixing promoted nutrient uptake and growth of Skeletonema costatum, which could be attributed to the break of the diffusion-limited resource concentration boundary layer surrounding phytoplankton.

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Frequency design of LEO-based navigation augmentation signals for dual-band ionospheric-free ambiguity resolution - Fujian Ma; Xiaohong Zhang; Jiahuan Hu; Pan Li; Lin Pan; Siqi Yu; Zhiyu Zhang (GPS Solutions, 2022)

Morphological and phylogenetic analysis of a new Melosira species and revision of freshwater Melosira in China - Lin Yang; Pan Yu; Qingmin You; Guisheng Li; Quanxi Wang (Journal of Oceanology and Limnology, 2022)

The Rapidly Evolving Fudu Estuary Sandbar Lagoon Landform on the East Coast of the Bohai Sea: Recent Changes and Mechanism - Lianjie Zhang; Jishun Yan; Bo Zhao; Xia Lin; Peng Wang; Chi Zhang; Yonghai Yu; Pan Zhang (Journal of Marine Science and Engineering, 2021)
The Fudu Estuary Sandbar Lagoon is one of the most representative sandbar-lagoon landforms in China, and has undergone drastic evolution in recent years, accompanied by increased coastal engineering activities. The evolution process and its control factors are studied through remote sensing interpretation and coastal sediment transport calculations. During 2010–2021, the sandbar quickly extended at an average speed of 49.5 m/a, but the annual growth has shown a decreasing trend in both area and width, and the shoreline has retreated by 25–45 m. The recent changes are the result of the combined action of natural conditions and human activities. Coastal sediment transport from west to east under the action of W-oriented waves is the natural cause of extension. An estuary dam and artificial island block the sediment transport path, and the material for the new growth of the sandbar comes from the erosion of its west side, which has directly caused the retreat and narrowing of the sandbar. The reduction in sediments from the river further aggravates the shrinkage. It is predicted that the sandbar will continue its eastward extension to connect with the coast in about 2–3 years. The erosion status is unlikely to change before the sediment supply is restored. Measures such as dismantling the estuary dam are recommended.

Correction to: A failure case study of tunnel water inrush source identified by statistical analysis model - Li-Gang Yuan; Xiao-Li Li; Xin Li; Yi-Lin Yu; Li-Guang Chen; Xian-Pan Xu; Xiang Wang (Arabian Journal of Geosciences, 2021)

High-throughput sequencing clarifies the spatial structures of microbial communities in cadmium-polluted rice soils - Li Song; Zhenzhi Pan; Yi Dai; Lin Chen; Li Zhang; Qilin Liao; Xiezhi Yu; Hongyan Guo; Guisheng Zhou (Environmental Science and Pollution Research, 2021)

A failure case study of tunnel water inrush source identified by statistical analysis model - Li-Gang Yuan; Xiao-Li Li; Xin Li; Yi-Lin Yu; Li-Gang Chen; Xian-Pan Xu; Xiang Wang (Arabian Journal of Geosciences, 2021)

Synthesis and biological evaluation of novel 1,3-diphenylurea quinoxaline derivatives as potent anticancer agents - Gui-Zhen Li; Xi-Lin Ouyang; Zu-Yu Mo; Yao Gu; Xiao-Lin Cao; Li Yang; Hai-Tao Tang; Ying-Ming Pan (Medicinal Chemistry Research, 2021)

Risk of two common glandular cell-type cancers (breast and colorectal cancers) in Chinese occupational chefs: a nationwide ecological study in Taiwan - Pei-Chen Lin; Chiung‑Yu Peng; Chih‑Hong Pan; Jui-Ying Lee; Tusty-Jiuan Hsieh; Yun-Shiuan Chuang; Robert J. Turesky; Chia-Fang Wu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2021)

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

Correction to: Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain - Shao-Ming Wang; Nino Goguadze; Yuriko Kimura; Yuko Yasui; Bin Pan; Tzu-Yun Wang; Yoki Nakamura; Yu-Ting Lin; Quinn H. Hogan; Katherine L. Wilson; Tsung-Ping Su; Hsiang-en Wu (Molecular Neurobiology, 2021)
A correction to this paper has been published: 10.1007/s12035-021-02310-3

Genomic Action of Sigma-1 Receptor Chaperone Relates to Neuropathic Pain - Shao-Ming Wang; Nino Goguadze; Yuriko Kimura; Yuko Yasui; Bin Pan; Tzu-Yun Wang; Yoki Nakamura; Yu-Ting Lin; Quinn H. Hogan; Katherine L. Wilson; Tsung-Ping Su; Hsiang-en Wu (Molecular Neurobiology, 2021)
Sigma-1 receptors (Sig-1Rs) are endoplasmic reticulum (ER) chaperones implicated in neuropathic pain. Here we examine if the Sig-1R may relate to neuropathic pain at the level of dorsal root ganglia (DRG). We focus on the neuronal excitability of DRG in a “spare nerve injury” (SNI) model of neuropathic pain in rats and find that Sig-1Rs likely contribute to the genesis of DRG neuronal excitability by decreasing the protein level of voltage-gated Cav2.2 as a translational inhibitor of mRNA. Specifically, during SNI, Sig-1Rs translocate from ER to the nuclear envelope via a trafficking protein Sec61β. At the nucleus, the Sig-1R interacts with cFos and binds to the promoter of 4E-BP1, leading to an upregulation of 4E-BP1 that binds and prevents eIF4E from initiating the mRNA translation for Cav2.2. Interestingly, in Sig-1R knockout HEK cells, Cav2.2 is upregulated. In accordance with those findings, we find that intra-DRG injection of Sig-1R agonist (+)pentazocine increases frequency of action potentials via regulation of voltage-gated Ca2+ channels. Conversely, intra-DRG injection of Sig-1R antagonist BD1047 attenuates neuropathic pain. Hence, we discover that the Sig-1R chaperone causes neuropathic pain indirectly as a translational inhibitor.

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

TDM-guided medication of polymyxin B in a patient with CRKP-induced bloodstream infection: a case report - Xuben Yu; Jingye Pan; Ziye Zhou; Xin Wen; Ying Dai; Guanyang Lin; Zheng Jiao; Chunhong Zhang (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Quantitative assessment on soil concentration of heavy metal–contaminated soil with various sample pretreatment techniques and detection methods - Fei Pan; Yong Yu; Lei Yu; Hailan Lin; Yeyao Wang; Linlin Zhang; Dawei Pan; Rilong Zhu (Environmental Monitoring and Assessment, 2020)

Small RNA profiling reveal regulation of microRNAs in field peanut pod rot pathogen infection - Mian Wang; Chao-xin Zhang; Li-juan Pan; Tong Wang; Na Chen; Ming-na Chen; Zhen Yang; Xin-gang Guo; Shan-lin Yu; Xiao-yuan Chi (Biologia, 2020)

Effects of Elevated Ozone Concentrations on Root Characteristics and Soil Properties of Elaeocarpus sylvestris and Michelia chapensis - Lan Pan; Wan-qi Lin; Ming Yu; Gan-wen Lie; Li Xue; Hong-yue Chen (Bulletin of Environmental Contamination and Toxicology, 2020)

Correction to: Development of recombinase polymerase amplification assay for rapid detection of Meloidogyne incognita, M. javanica, M. arenaria, and M. enterolobii - Yuliang Ju; Yu Lin; Guogen Yang; Huiping Wu; Yuemin Pan (European Journal of Plant Pathology, 2020)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Development of recombinase polymerase amplification assay for rapid detection of Meloidogyne incognita, M. javanica, M. arenaria, and M. enterolobii - Yuliang Ju; Yu Lin; Guogen Yang; Huiping Wu; Yuemin Pan (European Journal of Plant Pathology, 2019)

A Bregman adaptive sparse-spike deconvolution method in the frequency domain - Shu-Lin Pan; Ke Yan; Hai-Qiang Lan; Zi-Yu Qin (Applied Geophysics, 2019)

Resource (Light and Nitrogen) and Density-Dependence of Seaweed Growth - Xi Xiao; Susana Agusti; Fang Lin; Caicai Xu; Yan Yu; Yaoru Pan; Ke Li; Jiaping Wu; Carlos M. Duarte (Frontiers in Marine Science, 2019)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

Development of Multi-axis Motor Control Systems for Lower Limb Robotic Exoskeleton - Cheng-Tang Pan; Chun-Chieh Chang; Pei-Yuan Sun; Cheng-Lung Lee; Tzu-Chieh Lin; Chung-Kun Yen; Yu-Sheng Yang (Journal of Medical and Biological Engineering, 2019)

Comparative Study of ROCK1 and ROCK2 in Hippocampal Spine Formation and Synaptic Function - Jinglan Yan; Youcan Pan; Xiaoyan Zheng; Chuanan Zhu; Yu Zhang; Guoqi Shi; Lin Yao; Yongjun Chen; Nenggui Xu (Neuroscience Bulletin, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Effect of Partial Root-Zone Drying Irrigation (PRD) on the Gas Exchange and Antioxidant Enzymatic Activities in Alfalfa - Jing Zhang; Hui Xia Liu; Xiao Pan Pang; Cheng Yu; Qian Wang; Yu Pei Zhou; Li Guo Lin; Zheng Gang Guo (Journal of Soil Science and Plant Nutrition, 2019)

Gender differences and lung cancer risk in occupational chefs: analyzing more than 350,000 chefs in Taiwan, 1984–2011 - Pei-Chen Lin; Chiung-Yu Peng; Chih-Hong Pan; Pi-I Debby Lin; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Yak and Tibetan sheep trampling inhibit reproductive and photosynthetic traits of Medicago ruthenica var. inschanica - Hong Xiao; Zhen Peng; Chang Lin Xu; De Gang Zhang; Jin Long Chai; Tao Tao Pan; Xiao Jun Yu (Environmental Monitoring and Assessment, 2018)

Localization of Maize Critical N Curve and Estimation of NNI by Chlorophyll - Xiao-Gui Liang; Zuo-Lin Zhang; Li-Li Zhou; Si Shen; Zhen Gao; Li Zhang; Shan Lin; Yu-Qiang Pan; Shun-Li Zhou (International Journal of Plant Production, 2018)

Screening of seaweeds in the East China Sea as potential bio-monitors of heavy metals - Yaoru Pan; Thomas Wernberg; Thibaut de Bettignies; Marianne Holmer; Ke Li; Jiaping Wu; Fang Lin; Yan Yu; Jiang Xu; Chaosheng Zhou; Zhixing Huang; Xi Xiao (Environmental Science and Pollution Research, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Glycosaminoglycans from fish swim bladder: isolation, structural characterization and bioactive potential - Yongxi Pan; Peipei Wang; Fuming Zhang; Yanlei Yu; Xing Zhang; Lei Lin; Robert J. Linhardt (Glycoconjugate Journal, 2018)

The Effect of Sodium Fluoride on Cell Apoptosis and the Mechanism of Human Lung BEAS-2B Cells In Vitro - Jun Ying; Jie Xu; Liping Shen; Zhijie Mao; Jingchen Liang; Shuangxiang Lin; Xinyan Yu; Ruowang Pan; Chunxia Yan; Shengbin Li; Qiyu Bao; Peizhen Li (Biological Trace Element Research, 2017)

The association study of nonsyndromic cleft lip with or without cleft palate identified risk variants of the $$\varvec{GLI3}$$ G L I 3 gene in a Chinese population - Yirui Wang; Yimin Sun; Yongqing Huang; Yongchu Pan; Bing Shi; Jian Ma; Lan Ma; Feifei Lan; Yuxi Zhou; Jiayu Shi; Jinfang Zhu; Hongbing Jiang; et al. (Journal of Genetics, 2017)

CSF-Based Analysis for Identification of Potential Serum Biomarkers of Neural Tube Defects - Xinyu Yan; Lixin Mai; Changchun Lin; Wenji He; Gengsheng Yin; Jiakang Yu; Lian Huang; Sanqiang Pan (Neuroscience Bulletin, 2017)

Overexpression of a chrysanthemum transcription factor gene DgNAC1 improves the salinity tolerance in chrysanthemum - Ke Wang; Ming Zhong; Yin-huan Wu; Zhen-yu Bai; Qian-yu Liang; Qing-lin Liu; Yuan-zhi Pan; Lei Zhang; Bei-bei Jiang; Yin Jia; Guang-li Liu (Plant Cell Reports, 2017)

Static Magnetic Field Increases Survival Rate of Thawed RBCs Frozen in DMSO-Free Solution - Yi-June Lo; Yu-Hwa Pan; Chun-Yen Lin; Wei-Jen Chang; Haw-Ming Huang (Journal of Medical and Biological Engineering, 2017)

Tracking fluorescent components of dissolved organic matter from soils in large-scale irrigated area - Hongwei Pan; Huibin Yu; Yonghui Song; Lin Zhu; Ruixia Liu; Erdeng Du (Environmental Science and Pollution Research, 2017)

Making a queen: an epigenetic analysis of the robustness of the honeybee ( A pis mellifera ) queen developmental pathway - Xu Jiang He; Lin Bin Zhou; Qi Zhong Pan; Andrew B. Barron; Wei Yu Yan; Zhi Jiang Zeng (Molecular Ecology, 2017)
Specialized castes are considered a key reason for the evolutionary and ecological success of the social insect lifestyle. The most essential caste distinction is between the fertile queen and the sterile workers. Honeybee ( A pis mellifera ) workers and queens are not genetically distinct, rather these different phenotypes are the result of epigenetically regulated divergent developmental pathways. This is an important phenomenon in understanding the evolution of social insect societies. Here, we studied the genomic regulation of the worker and queen developmental pathways, and the robustness of the pathways by transplanting eggs or young larvae to queen cells. Queens could be successfully reared from worker larvae transplanted up to 3 days age, but queens reared from older worker larvae had decreased queen body size and weight compared with queens from transplanted eggs. Gene expression analysis showed that queens raised from worker larvae differed from queens raised from eggs in the expression of genes involved in the immune system, caste differentiation, body development and longevity. DNA methylation levels were also higher in 3‐day‐old queen larvae raised from worker larvae compared with that raised from transplanted eggs identifying a possible mechanism stabilizing the two developmental paths. We propose that environmental (nutrition and space) changes induced by the commercial rearing practice result in a suboptimal queen phenotype via epigenetic processes, which may potentially contribute to the evolution of queen–worker dimorphism. This also has potentially contributed to the global increase in honeybee colony failure rates.

Modulation of Nav1.8 by Lysophosphatidic Acid in the Induction of Bone Cancer Pain - Hai-Li Pan; Ben-Long Liu; Wei Lin; Yu-Qiu Zhang (Neuroscience Bulletin, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Piperine potentiates the effects of trans-resveratrol on stress-induced depressive-like behavior: involvement of monoaminergic system and cAMP-dependent pathway - Ying Xu; Chong Zhang; Feiyan Wu; Xiaoxiao Xu; Gang Wang; Mengmeng Lin; Yingcong Yu; Yiran An; Jianchun Pan (Metabolic Brain Disease, 2016)

Tectonic evolution of Tarim basin in Cambrian–Ordovician and its implication for reservoir development, NW China - Yu BINGSONG; RUAN ZHUANG; ZHANG CONG; PAN YINGLU; LIN CHANGSONG; WANG LIDONG (Journal of Earth System Science, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Antidepressant-like effects of ferulic acid: involvement of serotonergic and norepinergic systems - Jianliang Chen; Dan Lin; Chong Zhang; Gaowen Li; Nianping Zhang; Lina Ruan; Qizhi Yan; Jianxin Li; Xuefeng Yu; Xupei Xie; Cong Pang; Liang Cao; et al. (Metabolic Brain Disease, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Global and local brain network reorganization in attention-deficit/hyperactivity disorder - Pan Lin; Jubao Sun; Gang Yu; Ying Wu; Yong Yang; Meilin Liang; Xin Liu (Brain Imaging and Behavior, 2014)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Effects of Bone Marrow Mesenchymal Stem Cells on Hematopoietic Recovery and Acute Graft-Versus-Host Disease in Murine Allogeneic Umbilical Cord Blood Transplantation Model - Zhen Yu Li; Chun Qing Wang; Guang Lu; Xiu Ying Pan; Kai Lin Xu (Cell Biochemistry and Biophysics, 2014)

Pulmonary Toxicity in Mice Following Exposure to Cerium Chloride - Jie Hong; Xiaohong Yu; Xiaoyu Pan; Xiaoyang Zhao; Lei Sheng; Xuezi Sang; Anan Lin; Chi Zhang; Yue Zhao; Suxin Gui; Qingqing Sun; Ling Wang; et al. (Biological Trace Element Research, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Expression characterization and promoter activity analysis of the tilapia (Oreochromis niloticus) myosin light chain 3 promoter in skeletal muscle of fish - Yu-Ho Lin; Kuan-Chieh Peng; Chieh-Yu Pan; Zhi-Hong Wen; Jyh-Yih Chen (Transgenic Research, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Piperine potentiates the antidepressant-like effect of trans-resveratrol: involvement of monoaminergic system - Wu Huang; Zhuoyou Chen; Qiandong Wang; Mengmeng Lin; Shujuan Wu; Qizhi Yan; Fan Wu; Xuefeng Yu; Xupei Xie; Gaowen Li; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

HOXA9 Gene Expression in Acute Myeloid Leukemia - De-Peng Li; Zhen-Yu Li; Wei Sang; Hai Cheng; Xiu-Ying Pan; Kai-Lin Xu (Cell Biochemistry and Biophysics, 2013)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

Transcriptome profiling of the developing postnatal mouse testis using next-generation sequencing - Wei Gong; LinLin Pan; Qiang Lin; YuanYuan Zhou; ChengQi Xin; XiaoMin Yu; Peng Cui; SongNian Hu; Jun Yu (Science China Life Sciences, 2013)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Isolation and characterization of a long-chain acyl-coenzyme A synthetase encoding gene from the marine microalga Nannochloropsis oculata - Lin Zhang; Xiaolei Ma; Guanpin Yang; Baohua Zhu; Jichang Han; Wengong Yu; Kehou Pan (Journal of Applied Phycology, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Molecular characterization of β-lactam-resistant Escherichia coli isolated from Fu River, China - Li-Kou Zou; Li-Wen Li; Xin Pan; Guo-Bao Tian; Yan Luo; Qi Wu; Bei Li; Lin Cheng; Jiu-Jing Xiao; Su Hu; Yang Zhou; Yu-Juan Pang (World Journal of Microbiology and Biotechnology, 2012)

Effect of nonylphenol on response of physiology and photosynthesis-related gene transcription of Chlorella vulgaris - Haifeng Qian; Xiangjie Pan; Shutian Shi; Shuqiong Yu; Haiyan Jiang; Zhifan Lin; Zhengwei Fu (Environmental Monitoring and Assessment, 2011)

Verapamil exerts biphasic modulation on phenobarbital transport across the blood–brain barrier: evidence from an in vivo and in vitro study - Dan Yao; Zhi-Hong Yang; Li Liu; Jia Li; Yun-Li Yu; Lu-Lu Zhang; Xian Pan; Xiao-Dong Liu; Lin Xie; Guang-Ji Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Phylogenetic position of a threatened stag beetle, Lucanus datunensis (Coleoptera: Lucanidae) in Taiwan and implications for conservation - Chung-Ping Lin; Jen-Pan Huang; Yat-Hung Lee; Ming-Yu Chen (Conservation Genetics, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Cu(II): a “signaling molecule” of the mangrove endophyte Fusarium oxysporum ZZF51? - Jia-hui Pan; Yong-cheng Lin; Ni Tan; Yu-cheng Gu (BioMetals, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Baicalein attenuates intimal hyperplasia after rat carotid balloon injury through arresting cell-cycle progression and inhibiting ERK, Akt, and NF-κB activity in vascular smooth-muscle cells - Chieh-Yu Peng; Shiow-Lin Pan; Ying-Wen Huang; Jih-Hwa Guh; Ya-Ling Chang; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Effects of magnesium sulfate on dynamic changes of brain glucose and its metabolites during a short-term forced swimming in gerbils - Shiu-Min Cheng; Dar-Yu Yang; Chien-Pin Lee; Hung-Chuan Pan; Mao-Tsun Lin; Ssu-Hua Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2007)

Ex vivo expansion and pluripotential differentiation of cryopreserved human bone marrow mesenchymal stem cells - Ying Xiang; Qiang Zheng; Bing-bing Jia; Guo-ping Huang; Yu-lin Xu; Jin-fu Wang; Zhi-jun Pan (Journal of Zhejiang University-SCIENCE B, 2007)

Reduction in the in vitro expression of Brain–Pancreas Relative Protein by oxygen and glucose-deprivation - Yan-Hua Lin; Ai-Hua Liu; Yan Pan; Christel Westenbroek; Gert J Ter Horst; He-Ming Yu; Xue-Jun Li (Molecular and Cellular Biochemistry, 2007)

Organization and promoter analysis of a tiger shrimp Penaeus monodon single WAP domain-containing protein gene - Jyh Yih CHEN; Jian Chyi CHEN; Sheng Hwa LIN; Chia Yu PAN; Ching Ming KUO (Fisheries Science, 2006)

Identification of the Apoptosis Inhibitor Gene p49 of Spodoptera litura Multicapsid Nucleopolyhedrovirus - Mei Yu; Zhaofei Li; Kai Yang; Tiehao Lin; Yingxue Gong; Lijing Pan; Yi Pang (Virus Genes, 2005)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)